Empowerment of Aisyiyah members through the application of GERMAS on aspects of drug storage at home - Wibowo, Much Ilham Novalisa Aji; Juwita, Dina Ratna (Community Empowerment, 2021)
The government has implemented the Healthy Living Community Movement (GERMAS) program through promotion of the pharmaceutical sector related to drug storage at home. However, there are still many problems in storing household medicines in the community. This activity was carried out through a community empowerment approach using the community capacity building method for a community organization, Aisyiyah, which consists of Muslim women in the Grendeng village, Purwokerto. This activity ws carried out in stages, namely pre-test methods, lectures, group teaching, self-empowerment through peer teaching and training, and measuring the success of activities using post-tests. Based on the whole series of activities, the knowledge of partners about storing medicines at home has increased in a good category.